Institutions and the Diversity and Prevalence of Multinationals' Knowledge‐Augmenting Subsidiaries. (16th August 2017) - Allen, Matthew M. C.; Allen, Maria L.; Lange, Knut
Abstract: Multinational corporations (MNCs) increasingly seek to gain access to, and exploit, locationally specific sources of advanced knowledge and technological capabilities, creating a need to explain (1) the diversity among these facilities and (2) how institutions influence MNCs' abilities to invest in different subsidiary types. Extending debates on firms' knowledge‐augmenting activities, the authors integrate institutions into their analytical framework to a greater extent than previous work has done. Moreover, existing contributions provide typologies of R&D subsidiaries. In contrast, the authors focus on a particular subset of subsidiaries, knowledge‐augmenting ones, and put forward a theory to explain their variety and their prevalence, enabling them to identify previously neglected subsidiary types that have important managerial and policy implications. By downplaying the diversity of these subsidiaries, existing work has not been able to capture the full range of managerial challenges as well as the costs and benefits of different subsidiary types to host countries. The authors, therefore, problematize firms' abilities to gain access to foreign knowledge‐generating assets, highlight the importance of institutional environments, provide policy recommendations and identify areas for future research.